Influencia de la violencia familiar en el maltrato infantil de los niños y adolescentes del programa "mamis" en el hospital regional docente las mercedes - provincia de chiclayo, region lambayeque: 2014 - Chavez Quispe, Raquel Esmeralda (2015)
This thesis was carried out in order to analyze the influence of family violence in child maltreatment of children and adolescents in the Moms program at the Hospital Regional Docente Las Mercedes - province of Chiclayo, Lambayeque Region, in the period to 2014. It has been considered the type of applied research, taking as a basis an explanatory design, and sample consisted of 30 children and adolescents, which is worked by applying methods and techniques of quantitative and qualitative research. Of the obtained results it is possible to deduce that the familiar violence generates infantile maltreatment by means of physical and psychological aggressions to the children and adolescents causing them you would be injuries in its body and mental health. Finally, we consider that emotional health policies should be directed towards the incorporation of parents in the fulfilment of their roles for the integral formation of their children and prevent psychological frames in the future of their children.